"How Dare Men Mix up the Bible so with Their Own Bad Passions": When the Good Book Became the Bad Book in the American Civil War. (15th March 2022) - Brummitt, Jamie L.
Abstract: This essay examines how the American Civil War (1861–1865) transformed the material nature of the Bible such that some copies did not operate in the ways Anglo-Americans expected them to work as the inspired words of God. According to U.S. law, Bibles shipped to the Confederate States were contraband: illegal objects that should be confiscated before reaching enemy hands. Classifying Bibles as contraband led to the widespread notion that Bibles assumed national identities in their work for God. Protestants marked and printed Bibles as war objects that worked specifically for (or against) the Confederate States or the United States. They deployed these Bibles against other Protestants as powerful weapons of God. According to some, Bibles of enemy Protestants operated as immoral books that threatened to undermine God, God's people, and the military victory of God's favored nation. Thus, Bibles realized multiple and, sometimes, competing material natures. Confederate and Union Protestants put Bibles to work as powerful objects that mediated God's presence on earth, materialized debates over slavery, killed enemies, and stopped bullets. Some Bibles functioned simultaneously as God's Word, commodities, contraband, weapons, shields, and talismans. Each side attempted to hinder the progress and agency of enemy Bibles by capturing volumes as prisoners of war, stealing copies as souvenirs, and destroying books as powerful enemy weapons. The harsh and violent realities of the Civil War initiated a crisis in the material nature of Bibles such that some copies of the Good Book transformed into the Bad Book.